2009
DOI: 10.1111/j.1365-313x.2009.03873.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in cells around veins of the C3 plant Arabidopsis thaliana is important for both the shikimate pathway and leaf senescence as well as contributing to plant fitness

Abstract: SUMMARYCells associated with veins of C 3 species often contain significant amounts of chlorophyll, and radiotracer analysis shows that carbon present in the transpiration stream may be used for photosynthesis in these cells. It is not clear whether CO 2 is also supplied to these cells close to veins via stomata, nor whether this veinal photosynthesis supplies carbon skeletons to particular metabolic pathways. In addition, it has not been possible to determine whether photosynthesis in cells close to veins of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 60 publications
4
54
0
Order By: Relevance
“…Despite the fact that a wide number of fruit mutants have been characterized that contain altered pigmentation (Isaacson et al, 2002;Barry and Giovannoni, 2006;Galpaz et al, 2008;Nashilevitz et al, 2010), we chose to manipulate the chlorophyll content by antisense inhibition of GSA in an attempt to minimize the influence of pleiotropic effects. This same approach has already been successfully applied to a number of species (Kannangara and Gough, 1978;Hö fgen et al, 1994;Ilag et al, 1994;Chen et al, 2003), while addressing the functionality of photosynthesis in the cells surrounding the veins of C3 plants was recently achieved using an analogous approach, but different target enzyme, in Arabidopsis (Janacek et al, 2009). Table I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that a wide number of fruit mutants have been characterized that contain altered pigmentation (Isaacson et al, 2002;Barry and Giovannoni, 2006;Galpaz et al, 2008;Nashilevitz et al, 2010), we chose to manipulate the chlorophyll content by antisense inhibition of GSA in an attempt to minimize the influence of pleiotropic effects. This same approach has already been successfully applied to a number of species (Kannangara and Gough, 1978;Hö fgen et al, 1994;Ilag et al, 1994;Chen et al, 2003), while addressing the functionality of photosynthesis in the cells surrounding the veins of C3 plants was recently achieved using an analogous approach, but different target enzyme, in Arabidopsis (Janacek et al, 2009). Table I.…”
Section: Discussionmentioning
confidence: 99%
“…With restricted photosynthesis in cells surrounding the veins of Arabidopsis, following an analogous approach to that described here, Janacek et al (2009) suggested a role for photosynthesis in shikimate biosynthesis in this tissue. Similarly, Rubisco was demonstrated to operate, in isolation from the CalvinBenson cycle enzymes, as part of a more efficient route of fatty acid biosynthesis in developing embryos of Brassica napus (Schwender et al, 2004).…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that chloroplasts in BS and M cells of rice contain similar amounts of RuBisCO [47]. Downregulation of chlorophyll synthase in cells associated with the vasculature of C 3 Arabidopsis thaliana showed that photosynthetic capacity of these cells makes an important contribution to plant growth and seed production [48]. Thus, although the BS in C 3 species is most commonly associated with controlling fluxes of nitrogen, sulfur and water into and out of the leaf [49,50], these results suggest photosynthetic activity contributes significantly to plant fitness.…”
Section: Characteristics Of the C 4 Pathway In C 3 Plantsmentioning
confidence: 99%
“…Cytosolic PPDK also functions in gluconeogenesis during Arabidopsis seed germination, using pyruvate from amino acid catabolism (14). Another function is to provide PEP to the shikimate pathway in cells surrounding the vasculature, using pyruvate from decarboxylation of organic acids in the transpiration stream (15).…”
mentioning
confidence: 99%